2014
DOI: 10.4238/2014.september.26.17
|View full text |Cite
|
Sign up to set email alerts
|

Association of vitamin D receptor BsmI gene polymorphism with risk of low bone mineral density in post-menopausal women: a meta-analysis

Abstract: ABSTRACT. The vitamin D receptor BsmI gene polymorphism is reportedly associated with low bone mineral density (BMD) in postmenopausal women, but results from previous studies are conflicting. In the present study, we investigated the association between this polymorphism and the risk of low BMD through a metaanalysis of published studies. A literature search of the Pubmed, Embase, and CNKI databases from inception through July 2013 was conducted. The meta-analysis was performed using the STATA 12.0 software. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Early work from Keen et al (45) and Spector et al (46) using UK Twin cohorts, as well as the work from Ferrari et al (47), led to the identification of common polymorphisms in the VDR as being associated with BMD and an important target for the treatment of osteoporosis. However, there have been conflicting results (48), and more importantly meta-analyses including this genetic variant have not found consistent evidence for its association with BMD variation or osteoporotic fracture risk (8, 4951). However, one Iranian study has shown a statistically significant association with the VDR SNP rs2228570 and BMD in females, though they did not examine the SNP rs731246.…”
Section: Discussionmentioning
confidence: 99%
“…Early work from Keen et al (45) and Spector et al (46) using UK Twin cohorts, as well as the work from Ferrari et al (47), led to the identification of common polymorphisms in the VDR as being associated with BMD and an important target for the treatment of osteoporosis. However, there have been conflicting results (48), and more importantly meta-analyses including this genetic variant have not found consistent evidence for its association with BMD variation or osteoporotic fracture risk (8, 4951). However, one Iranian study has shown a statistically significant association with the VDR SNP rs2228570 and BMD in females, though they did not examine the SNP rs731246.…”
Section: Discussionmentioning
confidence: 99%
“…These observed phenomena produce long-term mineral loss from the skeleton and low BMD. The initial studies by Morrison et al [26][27][28] suggested that the "B" allele of the BsmI RFLP-site is the risk allele associated with low BMD, other studies either could confirm this [29] , did not find any effect [30] , or reported the opposite (31) .…”
Section: Discussionmentioning
confidence: 99%